The Artificial Intelligence Era: The Role of Radiologic Technologists and Radiation Therapists - Miaad Saeed Alshahrani,; Malak Jamaan Alzahrani,; Rasha Zayd Rashed AL Sari‏,; Khoulah Mohammed Abdullah hussain,; Basil Ghazi Alotibi,; Ghazi Dhaher Alenezi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The most talked-about topic in medical imaging research today, both for diagnostic and therapeutic purposes, is unquestionably artificial intelligence (AI). AI has been used by researchers to quantitatively evaluate radiographic features and automatically identify intricate patterns in imaging data. AI has been applied to many image modalities utilized at various phases of treatment in radiation oncology. For example, tumor delineation and treatment evaluation. AI is the crucial component that increases the processing capacity of large volumes of medical images, hence revealing illness features that are invisible to the human eye.The main objective of this paper is to evaluate the application and usage of AI in medical imaging and Radiology and also to assess the role of Radiologist in the same.